2021
DOI: 10.1186/s12889-021-12060-5
|View full text |Cite
|
Sign up to set email alerts
|

The importance of adverse childhood experiences for labour market trajectories over the life course: a longitudinal study

Abstract: Background Transitioning from school to work is important in influencing people’s trajectories throughout their life course. This study investigated the extent to which adverse childhood experiences (ACEs) were associated with differences in labour market trajectories for young adults in the context of a Nordic child care regime with low levels of child poverty. Methods Information on labour market participation, educational events, and public tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
1
11
2
Order By: Relevance
“…Here, we show that a multi-ethnic cohort with a high rate of some college education (88%) and a higher-than-average median income ($72,303) shows a definitive association between the number of different ACEs experienced in childhood and adulthood BMI. It has been previously determined that lower educational level and lower income are both linked to higher BMI and a greater number of ACEs (Hajian-Tilaki and Heidari, 2010;Hermann et al, 2011;Cohen et al, 2013;Ogden et al, 2017;Hardcastle et al, 2018;Blair et al, 2019;Giano et al, 2021;Hansen et al, 2021;Haugland et al, 2021), which suggests that we may be underestimating the factors that impact BMI in the HNP. Via linear regression, we show that each 0.37 ACE experienced increases adult BMI levels by 1 kg/m 2 .…”
Section: Aces and Adult Obesity In The Hnpmentioning
confidence: 99%
“…Here, we show that a multi-ethnic cohort with a high rate of some college education (88%) and a higher-than-average median income ($72,303) shows a definitive association between the number of different ACEs experienced in childhood and adulthood BMI. It has been previously determined that lower educational level and lower income are both linked to higher BMI and a greater number of ACEs (Hajian-Tilaki and Heidari, 2010;Hermann et al, 2011;Cohen et al, 2013;Ogden et al, 2017;Hardcastle et al, 2018;Blair et al, 2019;Giano et al, 2021;Hansen et al, 2021;Haugland et al, 2021), which suggests that we may be underestimating the factors that impact BMI in the HNP. Via linear regression, we show that each 0.37 ACE experienced increases adult BMI levels by 1 kg/m 2 .…”
Section: Aces and Adult Obesity In The Hnpmentioning
confidence: 99%
“…12 14-16 Currently available evidence suggests that it is possible to distinguish between groups of young adults on the labour market, which may be differentiated in terms of labour market participation states, employment conditions and adversity exposure patterns. 15 These groups may require diverging policy strategies tailored to differences in exposure to adversity, as well as to the mechanisms through which adversities are associated with labour market participation and employment conditions. For example, young adults who experience maltreatment might be more often unemployed and on benefits due to ongoing mental health problems, 16 whereas those who experienced material deprivation might enter the labour market earlier due to lower educational attainment.…”
Section: Original Researchmentioning
confidence: 99%
“…Studies to date have shown that cumulative exposure to childhood adversity is associated with a variety of outcomes relevant to young adults’ working lives: unemployment,10 11 benefit recipiency,12 income,13 NEET (not in employment, education or training) and labour market participation trajectories 14–17. However, cumulative exposure conceptualisations of childhood adversity have been criticised for not providing evidence that is required to better understand the mechanisms through which adversity is associated with outcomes of interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations